THE TRANSFORMATION OF MAJAPAHIT TEMPLE ORNAMENTS INTO BATIK MOTIFS - Andhisti, Ken (ISI Press Institut Seni Indonesia Surakarta, 2022)
Batik ERNA Mojokerto is a hand-written Mojokerto-style batik renowned for incorporating a Majapahit theme into its batik production. Some of the names of the batik motifs, such as the Surya Majapahit, Alas Majapahit, and Bunga Cinta Majapahit, have Majapahit nuances. The uniqueness of Batik Erna motivates this study to formulate the following research problem: how to transform the shape of the Majapahit heritage ornaments into Batik ERNA motifs? The purpose of this descriptive qualitative study is to investigate ERNA Batik motifs. Observation and interviews were utilized for data collecting, whereas data was examined using domain, taxonomy, and component analysis. The results of this study show that Batik ERNA transforms the ornaments of Majapahit heritage, such as the shape of the temple, flora and fauna ornaments on the relief walls, and the Majapahit royal signs into its batik motifs. The ornaments and the temple shapes have inspired the creation of batik motifs. The transformation results can be seen in the batik motifs of Ukel Cambah, Surya Majapahit, Rawan Inggek, and Kembang Suruh.